The effect of planning managerial and ownership transfers on successful succession in family-owned business: A Tunisian Case - ABID, Ameni; HAMROUNI, Amel DAKOUMI; MBAREK, Mohamed Karim BEN HADJ (The journal of contemporary issues in business and government, 2021)
Research on both planning managerial and ownership transfers in family businesses is almost nonexistent. The purpose of this study is to shed light on the importance of managerial and ownership planning in the succession process and its significance to sustain firm performance in the long run. The research has used a qualitative unique case study. Semi-structured interviews were conducted with two effective successors in family- owned businesses. Event history analysis method is used to study the speeches. This research shows that both managerial and ownership planning are interrelated strategic issues that merit thought and action. However, many business owners make the mistake of creating one plan without accounting for the other. Management succession planning should include development, training and support of successors. Furthermore, findings also showed that the existence of internal governance mechanisms reduces conflicts and therefore has a positive effect on succession in family-owned business.